Financial Capital and MSME Going Concern in Banjarmasin: The Mediating Role of Business Mentoring - Hikmahwati Hikmahwati; Noor Romy Rahwani; Muhammad Ali Watoni; Mark Gabriel Wagan Aguilar (Yayasan Ilomata, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in emerging economies, yet their sustainability is frequently constrained by limited capital access and inadequate business support. While prior studies have examined these factors separately, empirical evidence on how business mentoring mediates the relationship between capital loans and MSME going concern remains limited. This study addresses that gap by examining the direct and indirect effects of capital loans and business mentoring on MSME sustainability in Banjarmasin, Indonesia. A quantitative associative causal design was employed, with survey data collected from 92 KUR participants selected through purposive sampling. PLS-SEM was selected given the exploratory model structure, small sample size, and the need to assess measurement and structural relationships simultaneously. Findings indicate that capital loans exert a positive and significant effect on going concern (path coefficient = 0.679; p < 0.05), explaining 45.3% of its variance alongside mentoring. In contrast, business mentoring shows no significant direct or mediating effect, with a low mean score of 2.70 suggesting limited program intensity across the sample. These results are bounded to the Banjarmasin context and do not support broader causal generalizations. They nonetheless highlight the need for more structured and context-responsive mentoring programs integrated with existing capital support schemes.